en - I Kadek Maesa Dwi Payana Putra; I Nyoman Sedeng (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2022)
This research was carried out based upon the habitual speaking attitude of Singaporeans in Singapore Colloquial English by adding discourse particles ah and lah. Data were gathered from Mothership YouTube channel in Mothership Hits the Streets section from January to December 2020. There were two objectives; finding out the types and explaining the assigned functions of discourse particles ah and lah of SCE found in Mothership videos. It was conducted through applying qualitative approach which observation, document analysis, discourse analysis, and descriptive-interpretative method were employed. Theories applied to this research were discourse particles classification by Wong (2004), roles of discourse particles by Low & Deterding (2003), and context of situation by Halliday & Hasan (1985). The results showed that four types of ah and three types of lah were used by Singaporeans as seen in the videos; perlocutionary ah, vocative ah, emphatic ah, ah as question marker, impositional lah, propositional lah, and persuasive lah. Two functions were identified; utterance-final marker and audible comma particle. On the frequencies, 38 occurrences of particle ah and 62 occurrences of particle lah.